Uji Kinerja Burner Gas LPG Mesin Stirling dengan Variasi Laju Aliran Udara - Jufrizal, Jufrizal; Siregar, Zufri Hasrudy; Saktisahdan, Tengku Jukdin; Putra, Bintang Kelana; Syahputra, Muhammad Novrin Rizky (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2022)
A burner is a tool used to heat the heater as a source of initial heat whose heat functions to drive the Stirling engine. The burner used in this test is self-designed. The purpose of this study was to determine the temperature profile, fuel consumption used, power on the burner, and the efficiency of the Stirling engine burner with variations in air flow rates. Variations in the airflow rate used in this study were 2 m/s, 2.5 m/s, and 3 m/s. This research method was carried out experimentally and analyzed by the water boiling test method. The results of the three variations of air flow rate show that the highest temperature occurs in the Stirling engine burner with an airflow rate of 3 m/s of 813,815℃, for fuel consumption with variations in air flow rate of 343 gr, Stirling engine burner power with variations in air flow rate 2 m/s, 2.5 m/s, and 3 m/s produce the same power of 4.48 kW, and the highest efficiency on the Stirling engine burner is obtained at an airflow rate of 3 m/s of 38.33%.